RELACIONES INTRAFAMILIARES Y DESARROLLO DE LA INTELIGENCIA EMOCIONAL DE LOS ESTUDIANTES DE BACHILLERATO DE LA UNIDAD EDUCATIVA “PUEBLO NUEVO” DEL CANTÓN BABAHOYO. - MACIAS CHAGUAY ERIKA YULISSA (2024)
The present research study analyzes the problem of intra-family relationships and the development of emotional intelligence, considering that at present the family represents a fundamental axis for social improvement, the general objective was established to determine how intra-family relationships affect the development of emotional intelligence of high school students of the “Pueblo Nuevo” Educational Unit of the Babahoyo canton, The methodology to be used will be of a basic type where sources of information are analyzed through bibliographic and documentary review, using a correlational method which argues what is found in the sources relating it to the context of the study problem, of non-experimental design, due to the non-manipulation of the variables, nor of its population which is made up of 90 students of the first, second and third year of high school. The results found through Pearson's correlation test showed that the variables have a significant, high and positive relationship of 0.824, and that there are 12.2% of cases that are at a low level of emotional intelligence and family relationships and that the majority 83.3% of the cases are at a medium level for both variables. The conclusion is that by not having an adequate family environment, the development of emotional intelligence is affected, affecting the quality of life of the students.